Foaming Phenomenon in Bench‐Scale Anaerobic Digesters. (1st April 2013) - Siebels, Amanda M.; Long, Sharon C.
Abstract : The Madison Metropolitan Sewerage District (The District) in Madison, Wisconsin has been experiencing seasonal foaming in their anaerobic biosolids digesters, which has occurred from mid‐November to late June for the past few years. The exact cause(s) of foaming is unknown. Previous research findings are unclear as to whether applications of advanced anaerobic digestion processes reduce the foaming potential of digesters. The object of this study was to investigate how configurations of thermophilic and acid phase‐thermophilic anaerobic digestion would affect foaming at the bench‐scale level compared to single stage mesophilic digestion for The District. Bench‐scale anaerobic digesters were fed with a 4 to 4.5% by dry weight of solids content blend of waste activated sludge (WAS) and primary sludge from The District. Foaming potential was monitored using Alka‐Seltzer and aeration foaming tests. The bench‐scale acid phase‐thermophilic digester had a higher foaming potential than the bench‐scale mesophilic digester. These results indicate that higher temperatures increase the foaming potential of the bench‐scale anaerobic digesters. The bench‐scale acid phase‐thermophilic digesters had a greater percent (approximately 5 to 10%) volatile solids destruction and a greater percent (approximately 5 to 10%) total solids destruction when compared to the bench‐scale mesophilic digester. Overall, for the full‐scale foaming experienced by The District, it appears that adding an acid phase or switching to thermophilic digestion would not alleviate The District's foaming issues.